Mitos orang suci dan kuasa atas alam - Valiant, Raymond (Sejarah dan Budaya: Jurnal Sejarah, Budaya, dan Pengajarannya, 2023)
The relationship between nature and humans has given rise to various narratives not only limited to scientific knowledge formation through rationalized instrumentation but also in the form of personal experiences narrated as myths. This article examines the myths associated with the hydrosphere in which humans live, particularly regarding the role of holy men in controlling water as a natural force. The Brantas Watershed in East Java was chosen as the research area, considering that water management and agriculture activities in this river basin date since the 8th century. Specifically, two myths related to holy men's endeavors in the Brantas Watershed are analyzed in this article to show the relationship between power and nature. The research concludes that myths within our hydrosphere are closely related to socio-political changes due to the power struggle over land ownership and water governance. The involvement of holy persons within this frame was an anthropologic response towards a social-political reality that could not be rationally perceived thus making it more viable to approached within a mythological process. Hubungan alam dan manusia memunculkan berbagai narasi yang tidak hanya terbatas pada pembentukan pengetahuan ilmiah melalui suatu instrumentasi rasional, namun juga dalam bentuk pengalaman secara pribadi yang secara kolektif dinarasikan sebagai mitos. Artikel ini menelaah mitos yang berhubungan dengan hidrosfer di mana manusia hidup, khususnya mengenai peran dari orang suci dalam mengendalikan kekuatan alam. Sebagai lokasi penelitian dipilih Daerah Aliran Sungai (DAS) Brantas di Jawa Timur, yang sejak abad VIII telah berkembang dalam sisi pemanfaatan sumber daya air dan lahan untuk kepentingan pertanian. Dua mitos yang berhubungan dengan orang suci di dalam DAS Brantas dianalisis dalam artikel ini untuk menunjukkan relasi kuasa dengan alam. Disimpulkan, mitos yang berkaitan dengan hidrosfer erat kaitannya terhadap perubahan sosial-politik karena adanya pergeseran kekuasaan atas lahan dan air. Pelibatan orang sakti merupakan respon antropologis terhadap realitas sosial-politik yang tidak dapat ditanggapi secara rasional sehingga didekati melalui sebuah proses mitologisasi.